PENGARUH DUKUNGAN KELUARGA TERHADAP TINGKAT KEPATUHAN MINUM OBAT PASIEN TUBERKULOSIS DI PUSKESMAS WILAYAH BANJARMASIN TENGAH - Mochammad Maulidie Alfiannor Saputera; Yugo Susanto; Soraya Soraya (Jurnal Insan Farmasi Indonesia, 2021)
Patients suffering from tuberculosis often experience failure in therapy, due to non-adherence to taking medication. An important factor in improving medication adherence is the presence of family support. The purpose of this study was to determine the relationship between family support and medication adherence in pulmonary tuberculosis patients at the Public Health Center Central Banjarmasin area. The research method uses a cross sectional approach. The time of the study was carried out in May - July 2018. The sample of this study from January-April 2018 who treated pulmonary TB were 77 people. The sampling technique used was saturated sampling/total sampling, so the sample obtained was 33 people. The research instrument using a questionnaire was analyzed using correlation analysis using the Chi-Square test (a<0.05). Based on the results of the study showed that the results of the correlation test showed 0.000 <0.05. This shows that there is a strong relationship between family support and medication adherence in pulmonary tuberculosis patients at the Public Health Center Central Banjarmasin area.